1987
DOI: 10.3758/bf03203767
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation/mathematical model of learning: Extension of DMOD from appetitive to aversive situations

Abstract: The computer simulation/mathematical model called DMOD, which can simulate over 35 different phenomena in appetitive discrete-trial and simple free-operant situations, has been extended to include aversive di~rete-trial situations. Learning (V) is calculated using a three-parameter equation .1V = a{j(A -V) (see Daly & Daly, 1982;Rescorla & Wagner, 1972). The equation is applied to three possible goal events in the appetitive (e.g., food)case and to three in the aversive (e.g., shock) case. The original goal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…DMOD has been used successfully to integrate over 60 appetitive and aversive learning phenomena (Daly & Daly, 1982, 1987, 1991). The model has also been used to predict behaviors in areas as diverse as (a) preference for unpredictable over predictable reward (Daly, 1985, 1986, 1989, in press) and (b) the behavioral changes in laboratory rats after they consumed salmon from Lake Ontario, which are environmentally contaminated with toxic chemicals (Daly, Hertzler, & Sargent, 1989).…”
Section: Description Of Dmodmentioning
confidence: 99%
“…DMOD has been used successfully to integrate over 60 appetitive and aversive learning phenomena (Daly & Daly, 1982, 1987, 1991). The model has also been used to predict behaviors in areas as diverse as (a) preference for unpredictable over predictable reward (Daly, 1985, 1986, 1989, in press) and (b) the behavioral changes in laboratory rats after they consumed salmon from Lake Ontario, which are environmentally contaminated with toxic chemicals (Daly, Hertzler, & Sargent, 1989).…”
Section: Description Of Dmodmentioning
confidence: 99%
“…In 1987, we published an extension of DMOD that applies to aversive conditioning (e.g., electric shocks). Simulations of over 60 different learning phenomena have now been published (see Daly, 1985Daly, , 1989Daly, , 1991aDaly, , 1992bDaly & Daly, 1987.…”
Section: Frustration Theory and Dmodmentioning
confidence: 99%
“…To condition T{;c, the lambda value is the discrepancy between the amount of frustration experienced (0 on a rewarded trial) and the amount of frustration expected (indexed by V.v) ' (See Daly & Daly, 1982, 1987 On the basis of the research results ofothers, three additional assumptions are made: (1) The importance of a negative event is greater than that ofa positive event (the lambda value for Vav is twice the discrepancy; see Daly & Daly, 1982, p. 446). (2) Negative but not positive V values show spatial generalization (we multiply Vav by .5 to determine the start speed measure assumed to be about 180 cm from the goal, and.…”
Section: Frustration Theory and Dmodmentioning
confidence: 99%
“…Only recently have studies been done to uncover the combination of conditions that result in a preference for the unpredictable reward situation: Daly (1985) showed that a small 1-pellet reward in the immediate reward condition resulted in a 75% preference for the unpredictable reward situation, whereas a large 15-pellet reward resulted in a 70% preference for the predictable reward situation. Only one theory predicts that subjects will prefer the unpredictable reward situation if rewards are small and not delayed: DMOD (Daly MODification of the Rescorla & Wagner, 1972, model; Daly & Daly, 1982, 1984, 1987). Computer simulations of this model showed that there is a preference for unpredictability due, in part, to blocking, which is reversed only when unpredicted nonreward is aversive.…”
mentioning
confidence: 99%